ANTAGONISM HETEROTROPHIC BACTERIA ISOLATED FROM ESTUARY OF SIAK RIVER AND SETTLED SEA OF SIAK REGENCY AGAINST PATHOGENIC BACTERIA - Andrei Putra Zirma; Feliatra Feliatra; Nursyirwani Nursyirwani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Heterotrophic bacteria is bacteria that use organic substances as its nutrition sources. Organic substances are obtained from the rest of other organisms, waste or substances contained in the body of other organisms. This study aims to determine the activity of heterotrophic bacteria against pathogenic bacteria (Vibrio alginolyticus, Aeromonas hydrophila and Pseudomonas sp.). Total amount of bacteria at station 1 was higher than station 2, those were 2.3 x 107 cfu / ml at station 1 and 1.8 x 107 cfu / ml at station 2. Statistical analysis using the simple linear regresion indicated that the correlation between the growth of heterotrophic bacteria on environmental parameters (DO, pH, temperature and salinity) was very weak of wich correlation value(r) was 0.20 for all parameters. Antagonism test against pathogenic bacteria found that there were 8 bacterial isolates wich potentially inhibited the growth of the three pathogenic bacteria, the isolates were A11, A12, A14, A19, A21, A22, A23 and A25 with the inhibition zone ranges 4,8 - 14,5 mm. From the DNA sequences with 16S rDNA method and BLAST analysis, the bacteria isolates were identified asKerstersia gyiorum, Kerstersia sp.,Enterococcus sp. and three isolates was unidentified possibly due to these species hadnot registered in GenBank or had never been identified beforeKey words: Heterotrophic Bacteria, Antagonism, Estuary, 16s rDNA